Studi Desain dan Simulasi Kekuatan Pisau Dalam Alat Pengupas Sabut Kelapa Sistem Mekanis - Pratama, Muh Fajar Nuh, Tri Widodo Besar Riyadi, ST., M.Sc., Ph.D, Nur Aklis, ST., M.Eng (2015)
This research aims to determine the characteristics of the peeler knife at coco mechanical systems include stripping force, knife design, stripping force analysis, the value of the stress and the value of deflection (displacement) through the Finite Element Method (FEM). The knife material has been middle (MS) and cast iron (CI). The research method consists of tensile test specimens to determine the material properties and subsequently incorporated into the Solidwork Premium SimulationXpress 2012 program. Variations include a contact angle of 30° and 45° vertical and horizontal directions, and variations of stripping angle 10°, 20°, 30°, 40° and 50°. The results showed higher vertical stripping force, the higher the stripping force horizontal. And the higher stress value and the vertical deflection, the lower the stress and the horizontal deflection. While the stress value and the vertical deflection occurs difference fluctuated against stripping corner. And horizontal stress and strain values decline as rising stripping corner. Style stripping knife (Fcmax) 114 N vertical direction and 132.5 N horizontal direction. In the vertical direction, the highest stress of 10.196 MPa (CI45°) and the lowest was 9.429 MPa (MS30°), the highest deflection 0.0321 mm (MS30°) and the lowest 0.0259 mm (CI30°). The highest stress 5.158 MPa at stripping angle of 50° (MS30 °) and the lowest was 3.215 MPa at stripping angle of 20° (MS30° and CI45 °), the highest deflection stripping 0.0255 mm at an angle of 50 ° (MS30 °) and the lowest at 0.0076 mm stripping angle of 10° (CI30°). In the horizontal direction, the highest stress of 24.365 MPa (MS30°) and the lowest was 24.138 MPa (CI45°), the highest deflection 0.1281 mm (MS45°) and the lowest is 0,103 mm (CI30°). The highest stress 12.806 10 MPa at stripping corner ° (CI30°) and the lowest was 6.824 MPa at stripping angle of 50° (MS30°), the highest deflection stripping 0.0882 mm at an angle of 10° (MS30° and MS45°) and lowest stripping 0.0709 mm at an angle of 50° (CI30° and CI45°). Keyword : paring knife, tensile testing, finite element method